Public Policies on Healthy Diet: Analyzing the Portuguese Experience - Bruno Almeida Marques; Alexandre Morais Nunes; João Ricardo Catarino (Dietetics, 2025)
In Portugal, public policies promoting a healthy diet have gained prominence in recent years, reflecting a growing concern with the population’s health status and its individual, social, economic, and political impact. These policies aim to mitigate the impact of inadequate eating habits as a determinant of health and the population’s disease burden. Based on a document analysis, the main objective of this article is to explore public healthy diet policies in Portugal following the 2017 implementation of the Estratégia Integrada para a Promoção da Alimentação Saudável (Integrated Strategy for the Promotion of a Healthy Diet), which is the primary guiding instrument for these policies. Among the most impactful legislative measures found in this sector, we highlight the reformulation of food products, food taxation, food marketing regulation, food incentives, and food labeling. Despite significant progress in promoting healthy diets, some challenges still remain, particularly the growing prevalence of behavior-related chronic non-communicable diseases, like obesity, such as the maintenance of a set of health determinants related to inadequate nutrition. Thus, the continuity and deepening of such policies, combined with continuous impact assessments, are crucial to ensuring a healthier future.